PEMBARUAN HUKUM ISLAM MELALUI KONSEP AL-TA’WÎL NASHR HAMID ABU ZAYD - Akh. Syaiful Rijal (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2015)
Abu Zayd reconstruct the concept of texts with linguistic approach (al-manhaj al-tahlîl al-lughawî) in the broadest sense, including hermeneutics and semeotics. For Abu Zayd, ta’wîl different tafsir. He looked ta'wil as productive and objective reading as opposed to talwin, which tendentious reading-ideological (qirâ'ah mughridah aydulûjiyyah). The implications of understanding ta'wil of Abu Zayd are: First, there is something missing in understanding the text of the Qur’an, the awareness of the historicity of religious texts, that he is the text linguistics and that language is a social and cultural product. Second, put the text in the context of the Qur'an as a whole. By doing this Abu Zayd hope that the